Pharmacist-led antibiotic interventions in infectious disease patients: a Pakistani tertiary care antimicrobial stewardship study - Ali Hassan; Naeem Ur Rehman; Sumeira Maqbool; Mehreen Arif (Journal of Pharmaceutical Policy and Practice)
Background Antibiotics are widely used medications among infectious disease patients; therefore, proper monitoring and assessment are critical for ensuring rational use. Antimicrobial stewardship addresses the rational and appropriate use of antibiotics, which reinforces overall health outcomes. Ongoing antimicrobial resistance scenarios are an alarming condition for healthcare, necessitating continued practice of such assessments.Objectives To evaluate the use of antibiotics in patients with infectious diseases, implement and evaluate clinical pharmacy interventions that adhere to antimicrobial stewardship protocols.Methods A before and after study was designed to evaluate clinical pharmacy and antimicrobial stewardship interventions for infectious disease patients at a tertiary care hospital in Lahore. A Performa was designed for manual data collection. Study first identified the signal of error, implemented intervention and noted post-interventional followups.Results 102 infectious disease cases were analyzed in total and proposed 136 interventions. Physicians accepted 66% of the interventions (90) and rejected the remaining ones as unjustified. The most accepted intervention was the spectrum-based choice (n = 30), followed by de-escalation of dose (n = 17). Use of ceftriaxone was very high (54 Pt.), followed by vancomycin (30 Pt.).Conclusion Antimicrobial stewardship programmes are critical for any institution's proper health care system. It ensures proper antibiotic outflow to patients, thereby improving their health status. The role of pharmacists in establishing an AMS in a hospital setting is a highly commendable activity that enhances healthcare collaboration and outcomes. Clinical pharmacists should implement such activities to improve patient care.